Phako, phakonit, & laser phako : A quest for the best - Agarwal, Sunita; Agarwal, Athiya; Agarwal, Amar; Boyd, Benjamin F.; Boyd Samuel (Panamá : Highlights of ophthalmology, 2002)
Este libro se refiere a la cirugía de cataratas de incisión pequeña.
CONTENTS SECTION I: PRE-OPERATIVE EVALUATION, PHACOMACHINE AND PRELIMINARY STEPS SECTION II: PHACO TECHNIQUES SECTION III: PHACO IN DIFFICULT SITUATIONS SECTION IV: PHAKONIT & NO ANESTHESIA CATARACT SURGERY SECTION V: LASER PHAKO
Incluye índice
Incluye ilustraciones a color
Incluye bibliografía
Keywords: OFTALMOLOGÍA; OJOS -- CIRUGIA; CATARATA -- CIRUGÍA; CATARACT -- SURGERY